The Spectrum of Bacille Calmette–Guérin Diseases in Children—A Decade of Data from Neonatal Vaccination Settings - Noora Al Busaidi; Prakash KP; Amina Al-Jardani; Nashat Al-Sukaiti; Salem Al Tamemi; Bader Al-Rawahi; Zaid Al Hinai; Fatma Alyaquobi; Seif Al-Abri; Amal Al-Maani (Vaccines, 2021)
In this paper, we present a multicentre record-based descriptive study used to estimate the incidence and characterize the spectrum of confirmed bacille Calmette–Guérin (BCG) vaccine-related disease among children in Oman. This study included all children (age ≤ 14 years) who had culture and/or polymerase chain reaction (PCR)-confirmed BCG disease from January 2006 to December 2018, as identified from Central Public Health Laboratory data and International Classification of Diseases coding of an electronic patient information system. In total, 88 children confirmed to have BCG disease were included in the study, making an average incidence of 9.2 cases per 100,000 vaccinated neonates. The males comprised 65.9%, Omanis 93.2%, and the median age of presentation was 4 months in children with BCG disease. The most common type of disease was BCG abscesses (72.4%). Children with immunodeficiency and those presenting within 6 months were found to have a more severe and disseminated disease. In total, 28 children had immunodeficiency. The age of presentation and type of BCG disease was significantly associated with immunodeficiency status. The majority of cases required therapy (both medical and surgical) and recovered well. The incidence of laboratory-confirmed BCG vaccine-related disease was low in Oman supporting continuing the use of the BCG vaccination practice at birth.